SYNERGISTIC EFFECT OF COMBINATION BETWEEN CYANOMACLURIN AND ARTOCARPIN FROM ARTOCARPUS HETEROPHYLLUS HEARTWOODS AGAINSTS STREPTOCOCCUS PYOGENES AND STAPHYLOCOCCUS EPIDERMIDIS - Abdi Wira Septama; Eldiza Puji Rahmi, M.Sc (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Streptococcus pyogenes and Staphylococcus epidermidis are major problem of human health and may generate antibacterial resistance problem. Flavonoid has been used for the treatment of several ailments including bacterial infection. Artocarpus heterophyllus is a potential source of flavonoid compounds such as artocarpin and cyanomaclurin. The study was conducted to observe synergistic effects between flavonoid compounds against S. pyogenes and S. epidermidis. The antibacterial activity of combination of artocarpin and cyanomaclurin isolated from A. heterophyllus heartwoods were evaluated against S. pyogenes and S. epidermidis using broth microdilution methods. Interaction between two compounds in combination was determined using checkerboard assay. Artocarpin showed strong antibacterial activity with MIC value of 1.9 µg/mL. Cyanomaclurin only exhibited moderate activity with MIC value of 15.6 µg/mL. The mixture of compounds in several ratios tended to increase antibacterial activities of cyanomaclurin. There is no antagonistic effect when compounds used together. It can be concluded that flavonoid compounds in combination may enhance antibacterial activity to prevent development of antibacterial resistance.